2013
DOI: 10.1097/jto.0b013e31827bd7f5
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Non–Small-Cell Lung Cancer among California Hispanics According to Neighborhood Socioeconomic Status

Abstract: For California Hispanics, higher nSES was strongly associated with increased NSCLC incidence in women, but weakly associated in men, and ever-smoking rates were strongly correlated with increased acculturation. This finding may portend an increasing burden of NSCLC in Hispanic women, given future trends in acculturation and SES.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 31 publications
2
13
1
Order By: Relevance
“…Furthermore, we found some indications of a negative association with deprivation, with a decreased risk in the most deprived areas, more evident among women. Similar results were also found in populations at the earlier stages of the smoking epidemic [33,34]. Social inequalities in respiratory cancer incidence are largely explained by the social distribution of smoking habits.…”
Section: Discussionsupporting
confidence: 80%
“…Furthermore, we found some indications of a negative association with deprivation, with a decreased risk in the most deprived areas, more evident among women. Similar results were also found in populations at the earlier stages of the smoking epidemic [33,34]. Social inequalities in respiratory cancer incidence are largely explained by the social distribution of smoking habits.…”
Section: Discussionsupporting
confidence: 80%
“…We found that patients with higher education degree incurred a moderate decrease at the advanced stage at diagnosis. In fact, many studies revealed a similar association between education/income and cancer outcome and the impact varied by race/ethnic, smoking, insurance style, and cancer screening program [19,[26][27][28][29][30]. Moreover, the two studies suggested that more deprived patients were likely to present with more advanced-stage cancer in non-UHCS in the USA.…”
Section: Discussionmentioning
confidence: 99%
“…The socioeconomic measurements have proved useful to monitor health inequalities and can provide fundamental implications for prevention initiatives and resource allocation [16][17][18]. To date, the role of SES, either at individual or area level, in shaping lung cancer risk has only been examined from outside of China [9,12,[19][20][21]. Since each study has used different variables and different approaches to estimate individual or neighborhood socioeconomic conditions, the accumulated evidence is difficult to assess systematically in China.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have investigated ethnic differences in polymorphisms in genes involved in carcinogen metabolism such as CYP1A1 (14), CYP1B1 (15), and GSTM1 (16), and in DNA repair (17) and DNA damage signaling (18), with respect to lung cancer incidence. Socioeconomic aspects of the observed ethnic differences have also been investigated (19-21). A clear explanation for the observations cited above in the MEC has not yet emerged from these studies although it is recognized that some of these factors likely contribute.…”
Section: Introductionmentioning
confidence: 99%